Perancangan Sistem Infromasi Pencarian Layanan Fisioterapi Berbasis Android di Kota Pekanbaru - Bobi Handoko; Putri Indriani; Muhammad Firdaus; Marian Tonis (Jurnal Kesehatan Komunitas, 2026)
Physiotherapy services play a crucial role in the healing and rehabilitation of patients experiencing impaired motor function due to injury, illness, or post-surgery. However, in Pekanbaru City, information regarding the location, types of services, and schedules of physiotherapists is still limited, making it difficult for the public to obtain the services they need. This study aims to design and build an Android mobile application-based information system to facilitate the public in finding information on physiotherapy services in Pekanbaru. The method used is prototyping, which involves direct interaction between developers and users through an iterative feedback process. Data were collected through observation, interviews with physiotherapy service providers, and literature studies, then processed and compiled into a database. The results show that the SiTerapi application has a key feature in the form of a Google Maps-based search for clinic locations, polyclinics, and home care physiotherapy services with a distance radius feature. Based on the results of functional and feasibility tests, the application was declared to run well and is suitable for use as a medium for information on physiotherapy services in Pekanbaru. This application is expected to improve the accessibility and efficiency of the public in obtaining physiotherapy services according to their needs.